2016
DOI: 10.5603/ah.2016.0003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of arterial hypertension in patients scheduled for elective hip replacement

Abstract: Background: Assessment of blood pressure values and early diagnosis of hypertension are especially important in high-risk group, including patients in preoperative and postoperative period. The aim of the current study was the assessment of blood pressure values and prevalence of hypertension in patients undergoing elective hip replacement surgery-an orthopedic procedure associated with one of the highest cardiovascular complication rate. Material and methods: Two hundred and eighty-four consecutive patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Particular risk may be associated with orthopaedic surgery [4]. Orthopaedic procedures, especially total joint alloplasty, are major operations related to perioperative risk, as well as one of the highest rates of thromboembolic complications, and orthopaedic patients are usually at elevated CV risk [5,6]. Therefore, in these patients, early assessment and screening are of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…Particular risk may be associated with orthopaedic surgery [4]. Orthopaedic procedures, especially total joint alloplasty, are major operations related to perioperative risk, as well as one of the highest rates of thromboembolic complications, and orthopaedic patients are usually at elevated CV risk [5,6]. Therefore, in these patients, early assessment and screening are of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Greenky et al 25 also observed that in THA patients, age >75 years and hypertension significantly increase risks of complications and LOS. Szymanski et al 26 likewise noted that in THA patients, hypertension significantly increases risks of perioperative complications, including acute myocardial infarction, congestive heart failure, and stroke.…”
Section: Discussionmentioning
confidence: 97%